1987
DOI: 10.1172/jci113200
|View full text |Cite
|
Sign up to set email alerts
|

Osmoprotective activity for Escherichia coli in mammalian renal inner medulla and urine. Correlation of glycine and proline betaines and sorbitol with response to osmotic loads.

Abstract: Escherichia coli are protected against hypertonic NaCI by human urine. We have shown that this is due in part to the presence of glycine betaine and proline betaine. Several investigators have proposed that betaines and sorbitol are concentrated in the cells of the renal inner medulla where they exert a protective role against urea and extracellular osmotic forces. E. coli was used in the present studies as an "osmosensor" to detect osmoprotective activity in mammalian tissues. The greatest activity was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Possible reasons for these discrepancies are inherent differences between in vivo and in vitro study designs, differences among E. coli strains with regard to osmotolerance, and species differences in the content of urinary osmoprotective substances. For example, in 1 in vitro study, osmotically stressed E. coli were able to grow in hyperosmotic urine by utilization of urinary glycine and proline betaine as osmoprotective molecules. In that study, differences were found in urinary glycine and proline betaine concentrations among species resulting in differences in growth thresholds in a hyperosmotic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons for these discrepancies are inherent differences between in vivo and in vitro study designs, differences among E. coli strains with regard to osmotolerance, and species differences in the content of urinary osmoprotective substances. For example, in 1 in vitro study, osmotically stressed E. coli were able to grow in hyperosmotic urine by utilization of urinary glycine and proline betaine as osmoprotective molecules. In that study, differences were found in urinary glycine and proline betaine concentrations among species resulting in differences in growth thresholds in a hyperosmotic environment.…”
Section: Discussionmentioning
confidence: 99%
“…The development of such a hyperresistant state in enteric bacteria grown in media of high osmolarity and low oxygen content might have interesting ecological and sanitary implications. It is now well documented that both the intestinal content and the urine are media with high osmotic strengths (24,28,46) in which enteric bacteria can grow and exhibit structural and physiological adaptations to hyperosmolarity (5)(6)(7)24), such as OmpC porins (40) that lower the VNC response of E. coli in seawater (12). Moreover, the very high resistance to seawater of freshly voided fecal coliforms from human origin has been reported recently (13).…”
Section: Discussionmentioning
confidence: 99%
“…Current research on the role of bacterial osmoadaptation in urinary tract infection was triggered by the observation that urinary glycine betaine and proline betaine provide osmoprotection to E. coli (Chambers & Kunin, 1987). Glycine betaine raises the salt tolerance of E. coli to 1 M (according to the criterion described above; Kunin et al ., 1992).…”
Section: Introductionmentioning
confidence: 99%